Preclinical Safety Evaluation of AAV2-sFLT01— A Gene Therapy for Age-related Macular Degeneration - MacLachlan, Timothy K (Nature Publishing Group, 2011)
AAV2-sFLT01 is a vector that expresses a modified soluble Flt1 receptor designed to neutralize the proangiogenic activities of vascular endothelial growth factor (VEGF) for treatment of age-related macular degeneration (AMD) via an intravitreal injection. Owing to minimal data available for the intravitreal route of administration for adeno-associated virus (AAV), we initiated a 12-month safety study of AAV2-sFLT01 administered intravitreally at doses of 2.4 × 10(9) vector genomes (vg) and 2.4 × 10(10) vg to cynomolgus monkeys. Expression of sFlt01 protein peaked at ~1-month postadministration and remained relatively constant for the remainder of the study. Electroretinograms, fluorescein angiograms, and tonometry were assessed every 3 months, with no test article-related findings observed in any group. Indirect ophthalmoscopy and slit lamp exams performed monthly revealed a mild to moderate but self-resolving vitreal inflammation in the high-dose group only, which follow-up studies suggest was directed against the AAV2 capsid. Histological evaluation revealed no structural changes in any part of the eye and occasional inflammatory cells in the trabecular meshwork, vitreous and retina in the high-dose group. Biodistribution analysis in rats and monkeys found only trace amounts of vector outside the injected eye. In summary, these studies found AAV2-sFLT01 to be well-tolerated, localized, and capable of long-term expression.